Effectiveness of a physical activity program on cardiovascular disease risk in adult primary health-care users: the "Pas-a-Pas" community intervention trial - Victoria Arija; Felipe Villalobos; Roser Pedret; Angels Vinuesa; Mercé Timón; Teresa Basora; Dolors Aguas; Josep Basora; Pas- (BMC, 2017)
Abstract Background Physical activity is a major, modifiable, risk factor for cardiovascular disease (CVD) that contributes to the prevention and management of CVD. The aim of this study was to assess the short- and medium-term effectiveness of 9 months of a supervised physical activity program, including sociocultural activities, on CVD risk in adults. Methods Multicentered, randomized, controlled community intervention involving 364 patients in four primary care centers. The participants were randomly assigned to a Control Group (CG = 104) or Intervention Group (IG = 260); mean age 65.19 years; 76.8% women. The intervention consisted of 120 min/week walking (396 METs/min/week) and sociocultural gathering once a month. Clinical history, physical activity, dietary intake, CVD risk factors (smoking, systolic and diastolic blood pressure, weight, waist circumference, BMI, total cholesterol, LDL- and HDL-cholesterol, triglycerides, glycosylated hemoglobin and glucose) and global CVD risk were assessed at baseline and at the end of the intervention and multivariate models were applied to the data. Incidence of adverse cardiovascular events and continued adherence to the physical activity were assessed 2 years after intervention. Results At the end of the intervention period, in the IG relative to the CG group, there was a significant increase in physical activity (774.81 METs/min/week), a significant change during the intervention period in systolic blood pressure (−6.63 mmHg), total cholesterol (−10.12 mg/dL) and LDL-cholesterol (−9.05 mg/dL) even after adjustment for potential confounders. At 2 years after the intervention, in the IG, compared with the CG, tthe incidence of adverse cardiovascular events was significantly lower (2.5% vs. 10.5%) and the adherence to regular physical activity was higher (72.8% vs 27.2%) in IG compared to CG. Conclusions This community-based physical activity program improved cardiovascular health in the short- as well as medium-term, and promoted regular physical activity in the medium-term in older Spanish adults. Trials registration Clinicaltrials.gov ID NCT02767739 . Trial registered on May 5th, 2016. Retrospectively registered